Application of the Principles of Justice in the Distribution of Wealth: A Literature Review of Contemporary Islamic Economics - Fahrudin , Fahrudin (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research discusses the application of the principles of justice in wealth distribution in the context of Islamic economics, focusing on instruments such as zakat, sadaqah, and the prohibition of usury. These principles are recognized as key foundations in creating social justice and reducing economic disparities. However, despite their great potential theoretically, the application of these principles in practice often faces various challenges. This research uses a descriptive qualitative approach through a literature review to evaluate the extent to which these principles of justice are applied in the real world and to identify factors that hinder their implementation. The findings indicate a gap between theory and practice in the application of the principles of equity in wealth distribution. The main challenges faced include the lack of adequate regulation, inefficiencies in the management of zakat and alms, as well as the dominance of the conventional financial system which is not always in line with sharia principles. In addition, there are still differences in the understanding and application of these principles across different economic and social contexts, which complicates efforts to realize equitable wealth distribution. The implications of these findings emphasize the need for more effective regulatory and governance reforms to support the implementation of equity principles in Islamic economics. Policymakers are expected to develop a stronger legal framework, as well as improve Islamic financial literacy among the public. For economic actors, especially Islamic financial institutions, there is a need for innovation in financial products and services that truly reflect the spirit of social justice and not only focus on formal compliance with sharia. Thus, this study provides recommendations that can be used as a reference to improve the effectiveness of the application of the principles of justice in wealth distribution, in order to achieve broader and more sustainable social welfare. Keywords: Principles Equality, Distribution of Wealth Rights, Islamic Economics Abstrak Penelitian ini membahas penerapan prinsip-prinsip keadilan dalam distribusi kekayaan dalam konteks ekonomi Islam, dengan fokus pada instrumen seperti zakat, sedekah, dan larangan riba. Prinsip-prinsip ini diakui sebagai fondasi utama dalam menciptakan keadilan sosial dan mengurangi kesenjangan ekonomi. Namun, meskipun secara teoritis memiliki potensi besar, penerapan prinsip-prinsip ini dalam praktik sering kali menghadapi berbagai tantangan. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui kajian pustaka (literature review) untuk mengevaluasi sejauh mana prinsip-prinsip keadilan tersebut diterapkan di dunia nyata dan untuk mengidentifikasi faktor-faktor yang menghambat implementasinya. Hasil temuan menunjukkan adanya kesenjangan antara teori dan praktik dalam penerapan prinsip-prinsip keadilan dalam distribusi kekayaan. Tantangan utama yang dihadapi termasuk kurangnya regulasi yang memadai, inefisiensi dalam pengelolaan zakat dan sedekah, serta dominasi sistem keuangan konvensional yang tidak selalu sejalan dengan prinsip-prinsip syariah. Selain itu, masih terdapat perbedaan pemahaman dan penerapan prinsip-prinsip ini di berbagai konteks ekonomi dan sosial, yang memperumit upaya untuk mewujudkan distribusi kekayaan yang adil. Implikasi dari temuan ini menekankan perlunya reformasi regulasi dan tata kelola yang lebih efektif untuk mendukung penerapan prinsip-prinsip keadilan dalam ekonomi Islam. Pembuat kebijakan diharapkan dapat mengembangkan kerangka hukum yang lebih kuat, serta meningkatkan literasi keuangan syariah di kalangan masyarakat. Bagi pelaku ekonomi, terutama lembaga keuangan Islam, diperlukan inovasi dalam produk dan layanan keuangan yang benar-benar mencerminkan semangat keadilan sosial dan tidak hanya terpaku pada kepatuhan formal terhadap syariah. Dengan demikian, penelitian ini memberikan rekomendasi yang dapat digunakan sebagai acuan untuk meningkatkan efektivitas penerapan prinsip-prinsip keadilan dalam distribusi kekayaan, guna mencapai kesejahteraan sosial yang lebih luas dan berkelanjutan. Kata Kunci: Prinsip Kesetaraan, Distribusi Hak Kekayaan, Ekonomi Islam